Theory of International Economic Relations - Kukharyk, Viktoriia V. (My University, 2023)
The normative academic subject "Theory of International Economic Relations" is a complex discipline that provides for the formation of future specialists' system of special knowledge on the problems and prospects of the international economic relations development. The result of studying the discipline is: the formation of a holistic view of the processes that characterize the international level of national economies interaction; mastering the latest approaches to assessing the evolutionary nature of the international economic relations system development; mastering the culture of modern economic thinking.
Keywords: international economic relation